Suomen poliisi ja pohjoismaiset poliisipäällystökonferenssit 1930-luvulla - Pitkänen, Juho (Ennen ja nyt, 2026)
In the Finnish police, the Nordic countries served as an important reference group already in the 1920s. This cooperation became more structured in the 1930s, marked by the first Nordic police chief conferences, which fostered and intensified the collaboration. This article examines the Finnish police’s involvement in these conferences, drawing on official conference records, professional police journals, and Finnish archival materials. The article explores the motivations behind Finland’s participation and its impacts. The conferences embodied an interest in regional cooperation and were part of a broader trend of internationalization in the police. Conferences became a forum for joint planning and advocacy. In Finland, Nordic collaboration was regarded important, driven by professional needs and common threats. Police leadership sought to build personal networks, enhance cooperation to prevent crime, and improve domestic operations. The conferences provided ideas for the development of policing in Finland and strengthened cooperation and relations between police officers. Not all the plans were realized before the outbreak of the Second World War, but the conferences laid the foundations for cooperation after the war.